Alfabetização mediada por computador: uma experiência com o software Luz do Saber - Rocha, Joelma dos Santos Ramos (2016)
One of the great challenges of education has been to ensure the full literacy of students by the end of the third year of primary education. The need for special attention for students with poor academic performance in reading and writing is urgent. Unfortunately, difficulties in acquiring reading and writing tend to last for much of the elementary school walk, resulting in much disapproval. What practices can be applied to an effective acquisition in the reading and writing acquisition process of the non-literate students, who are in an age / grade gap, totally unmotivated for learning? The present work aims to plan and implement an Intervention Planning with a group of ten students, based on the use of the software Luz do Saber, with the aim of promoting the reading and writing learning of 3rd, 4th and 5th graders Years of elementary school in a rural public school in the city of Feira de Santana-BA, who did not learn to read and write at the right age. In this school, there is a high rate of students between the ages of 10 and 16 who have not been able to be literate, resulting in serious problems for students' school life. The Luz do Saber software is based on Paulo Freire's theory (2014 [19211997]), as well as the contributions of Emília Ferreiro and Ana Teberosky (1999) on the process of acquisition of the linguistic code. I bring the concept of language / language as a social interaction (Bakhtin, 1986, 2003). This was a research anchored in the presuppositions of a qualitative approach, through the research-intervention method whose researcher is part of the elaboration and execution of the research as subject implied in every process. The use of the computer has been shown as an excellent possibility as a tool for learning, as well as promoting the insertion in the digital culture and creating strategies for teachers and students to use this tool in a way that meets and meets their needs. The new technologies have been a significant element that has been taking great proportions and space in the lives of people, in their day to day, becoming a great possibility of insertion in the school context. The results of the research evidenced the effectiveness of the Luz do Saber software in the process of literacy and literacy of students.